Good governance and tourism development in Vietnam: looking back at the past three decades (1990–2023) - Hoang Thi Phuong Thao; Márta Bakucz (Cogent Business & Management, 2024)
Vietnam has become a popular international tourist destination since the 2010s, thanks to the successful implementation of the government's comprehensive innovative policies and the country's abundant resources. The interest of powerful nations in Vietnam has increased due to political stability and a preference for economic openness. This has resulted in the signing of numerous trade agreements across various countries and regions. As a result, the tourism sector has taken advantage of these opportunities and has become a crucial part of economic agendas, earning a strategic investment priority. This study aims to determine the impact of good governance on the development of the tourism industry. To achieve this, an Autoregressive Distributed Lag (ARDL) model was used with data from 1990 to 2023. The results indicate that variables such as the human development index, the rule of law, and tourism revenue have a positive long-term association. Contrary to expectations, the study found that the higher value of government effectiveness scores, foreign direct investment, and the export-to-GDP ratio have adverse effects on tourism revenue. The study aims to bridge the gap in understanding the relationship between the tourism industry and government efforts to build effective institutions and good governance. The main findings have significant policy implications and warrant further discussion.
Keywords: E02; N45; Z30; 650; Good governance; institutional theory; tourism development; ARDL model; Vietnam